PERFORMANCE OF BUSINESS EDUCATION GRADUATES IN ADMINISTRATIVE FUNCTIONS IN REGISTERED BUSINESS ESTABLISHMENTS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The purpose of this study is to assess the performance of university businesseducation graduates working in registered business establishments in Anambra State. Thepopulation consisted of 268 managers of 55 registered establishments that have businesseducation graduates in their employment. One research question and one hypothesistested at 0.05 level of significance were used. The instrument employed for data collectionwas fifteen item questionnaire. Descriptive statistics of mean and standard deviation wereemployed in analyzing data relative to the research question while t-test inferentialstatistics was employed in testing the hypothesis. The findings revealed that universitybusiness education graduates performed efficiently in 15 specified administrativefunctions and significant difference was not found in respondents' mean ratings as a resultof their establishments. It was concluded that the graduates studied performed efficientlyin administrative functions articulated in the study. It was recommended that the plannersand implementers of university business education programme should maintain theirstandards of nurturing their students to ensure continued efficient performance of thegraduates in employment